NUMERICAL MODELING OF DYNAMICS PRESSURE SOURCE OF SINABUNG VOLCANO BASED ON GPS DATA IN 2011-2016 - Kumalasari, Ratih
Sinabung Volcano has begun to erupt since August 27th, 2010 after 1200 years of dormant. The eruption continues until now (2019), so it is necessary to do an analysis to predict the position and volume of the pressure source. This study aims to predict the depth and volume of the magma chambers based on GPS data. The GPS data used included local data from continuous GPS observation stations belonging to the PVMBG (Center for Volcanology and Geological Disaster Mitigation) around Sinabung Volcano. Data were processed by GAMIT / GLOBK 10.6 software. The data were relatively tied to the SAMP station to reduce the effect of seismicity. Before the inversion, the period of data was divided based on the trend line of the time series. The research obtained 12 periods, then each of periods was inverted by Mogi and McTigue models on particle swarn optimization (PSO) and very fast simulated annealing (VFSA) schemes. The inversion of both schemes shows satisfactory results in terms of misfit as well as model responses. From the data analysis associated with seismic activity and geological conditions of Sinabung Volcano, three local pressure source locations were found, namely shallow magma chamber at a depth of about 0.5km-1.3 km, moderate magma chamber at 3.8 km and deep magma chamber at 16.5 km.